2015
DOI: 10.1186/s12885-015-1962-x
|View full text |Cite
|
Sign up to set email alerts
|

Methylation status of COX-2 in blood leukocyte DNA and risk of gastric cancer in a high-risk Chinese population

Abstract: BackgroundMethylation is a common epigenetic modification which may play a crucial role in cancer development. To investigate the association between methylation of COX-2 in blood leukocyte DNA and risk of gastric cancer (GC), a nested case–control study was conducted in Linqu County, Shandong Province, a high risk area of GC in China.MethodsAssociation between blood leukocyte DNA methylation of COX-2 and risk of GC was investigated in 133 GCs and 285 superficial gastritis (SG)/ chronic atrophic gastritis (CAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In several diseases, and cancer in particular, chromosomal deletions and amplifications are frequent 15 16 . Consequently, use of single-/low-copy genes for normalization was disfavoured a decade ago 17 , but they are still frequently used 18 19 20 21 22 23 . Here we confirm that use of single-/low-copy genes such as ACTB and COL2A1 can result in doubling and halving of PMR values ( Supplementary Table S4 ) for samples with known aberrations at these loci (ref.…”
Section: Discussionmentioning
confidence: 99%
“…In several diseases, and cancer in particular, chromosomal deletions and amplifications are frequent 15 16 . Consequently, use of single-/low-copy genes for normalization was disfavoured a decade ago 17 , but they are still frequently used 18 19 20 21 22 23 . Here we confirm that use of single-/low-copy genes such as ACTB and COL2A1 can result in doubling and halving of PMR values ( Supplementary Table S4 ) for samples with known aberrations at these loci (ref.…”
Section: Discussionmentioning
confidence: 99%
“…39 DNA methylation of COX2 gene was shown to be reduced in the blood of gastric cancer patients. 40 Also, the level of methylation was seen to be not constant and continuously changing during the hepatocytic progression into hepatocellular carcinoma. That was proposed to be motivated by the silencing of tumour-suppressor genes and the activation of key oncogenes.…”
Section: Discussionmentioning
confidence: 97%
“…To date, miRNAs have been demonstrated as a useful regulator in the development of some tumors, including cell growth, apoptosis, differentiation, invasiveness and migration, and usually serve as a kind of tumor suppressors [7][8][9][10][11]. It has been reported that the COX-2 expression can be found to be increased in a wide variety of tumors, such as human colorectal cancer, liver cancer, cervical cancer, and pancreatic cancer [16][17][18][19]. Some studies indicated that the expression of COX-2 has been thought as a useful tumor biomarker, and COX-2 exhibited the increased invasion potential in cancers.…”
Section: Discussionmentioning
confidence: 99%